Příklady z matematiky

Každé načítání stránky vám zadá nové příklady !




Jméno:_____________________________
 
X + Y - Z = 57
Z + Y + X = 89
Z + X - Y = 75

X=
Y=
Z=






X + Y - Z = 26
Z + Y + X = 214
Z + X - Y = 106

X=
Y=
Z=






X + Y - Z = 119
Z + Y + X = 173
Z + X - Y = 17

X=
Y=
Z=






X + Y - Z = 13
Z + Y + X = 37
Z + X - Y = 19

X=
Y=
Z=






X + Y - Z = 149
Z + Y + X = 151
Z + X - Y = 27

X=
Y=
Z=






X + Y - Z = 69
Z + Y + X = 227
Z + X - Y = 127

X=
Y=
Z=






X + Y - Z = -13
Z + Y + X = 163
Z + X - Y = 123

X=
Y=
Z=






X + Y - Z = 162
Z + Y + X = 168
Z + X - Y = 20

X=
Y=
Z=






X + Y - Z = 92
Z + Y + X = 156
Z + X - Y = -12

X=
Y=
Z=